A Rare Cause of Critical Carotid Stenosis. Issue 1 (March 2019) - Sentman, Michelle; Bloch, Charles; Sommerset, Jill; Bloch, Robert; Karmy-Jones, Riyad; Teso, Desarom
Blunt carotid artery injuries are uncommon, usually occur in a delayed fashion, and most commonly after significant blunt-force mechanism. Choke holds, use of pressure points, and other close-combat techniques used in military or mixed martial arts training can have the same kinetic impact as a motor vehicle crash. We present an unusual case of common carotid fibrosis which required surgery and suggest that duplex ultrasound might be an appropriate screening tool in those who regularly participate in such training.